2022
DOI: 10.3390/su14148705
|View full text |Cite
|
Sign up to set email alerts
|

Wind Speed Prediction Model Based on Improved VMD and Sudden Change of Wind Speed

Abstract: An accurate wind speed prediction system is of great importance prerequisite for realizing wind power grid integration and ensuring the safety of the power system. Quantifying wind speed fluctuations can better provide valuable information for power dispatching. Therefore, this paper proposes a deterministic wind speed prediction system and an interval prediction method based on the Lorentzian disturbance sequence. For deterministic forecasting, a variational modal decomposition algorithm is first used to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The VMD is an adaptive data decomposition method that is suitable for handling non-stationary sequence data [26,27]. It decomposes a sequence into a specific number of subsequences, and each subsequence holds its own center frequency and finite bandwidth.…”
Section: Optimal Variational Mode Decompositionmentioning
confidence: 99%
“…The VMD is an adaptive data decomposition method that is suitable for handling non-stationary sequence data [26,27]. It decomposes a sequence into a specific number of subsequences, and each subsequence holds its own center frequency and finite bandwidth.…”
Section: Optimal Variational Mode Decompositionmentioning
confidence: 99%
“…Most of these papers proposed models for locations in China, such as [21][22][23][24][25][26][27][28]. Six works proposed models for locations in the USA [29][30][31][32][33][34] and nine works for locations in Europe, such as Spain and Belgium [35][36][37][38][39][40][41][42][43]. Only one work was found that targeted the hot desert climate in which data from a wind farm in Pakistan was used [44].…”
Section: Related Workmentioning
confidence: 99%